Study of wound healing potential of Stevia rebaudiana ethanol extract in male rats - S. Goorani; M.M. Zangeneh*; A. Zangeneh; C. Poorshamohammad; M. Abiari; R. Moradi; F. Najafi; R. Tahvilian (Iranian Society of Pharmacognosy, 2018)
Background and objectives: Stevia rebaudiana has been used in medicine as anti-inflammatory, antioxidant, antipyretic, anti-fungal, and antibacterial agent. The present study was conducted to investigate the healing effects of S. rebaudiana ethanol extracts on cutaneous wounds in rats. Methods: Full-thickness excisional wounds (2×2 cm) were induced on the back of 32 rats. The rats were divided into four groups as follows; untreated (control) and treated with 1 mL basal cream, 1 mL S. rebaudiana ethanol extract 10%, and 1 mL tetracycline (3%) for 20 days (short term). Animals of each group were euthanized at 20 day post-injury and wounds were assessed through macroscopic and microscopic analyses. Results: During the experiment, S. rebaudiana indicated a significant reduction in the wound area compared to other groups. Parameters such as arrangement of the healing tissue, re-epithelilization and epithelial formation demonstrated considerable changes when compared to the control. In addition, treatment with S. rebaudiana decreased the total number of cells, fibrocytes/fibroblasts ratio, neutrophils, and lymphocytes and enhanced the number of blood vessels and fibroblasts at 20 day. Conclusion: The present study demonstrated the wound healing activity of S. rebaudiana, lending credence to the folkloric use in the treatment of cutaneous wounds.